Pharmacodynamic Monitoring of Mammalian Target of Rapamycin Inhibition by Phosphoflow Cytometric Determination of p70S6 Kinase Activity. Issue 1 (January 2015) - Hoerning, André; Wilde, Benjamin; Wang, Junyu; Tebbe, Bastian; Jing, Lu; Wang, Xinning; Jian, Fu; Zhu, Jiqiao; Dolff, Sebastian; Kribben, Andreas; Hoyer, Peter F.; Witzke, Oliver
<x xml:space="preserve">Abstract</x> Background Immunosuppressive therapy with mammalian target of rapamycin inhibitors (mTORi) requires maintenance of an effective inhibition of the alloimmune response, whereas reducing drug-related nephrotoxicity. Therapeutic monitoring is based on mTORi trough levels, which do not necessarily reflect biologic effects on the PI3K-Akt-mTOR pathway and hence may often result in under-immunosuppression or over-immunosuppression. Methods Phosphorylation of p70S6 kinase was studied by phosphoflow cytometry and by Western blot in both peripheral blood monocyte cells and CD3+ T cells of renal transplant recipients (RTX) receiving tacrolimus (n=34) or cyclosporine A (CsA) (n=24) or an mTORi (n=26). 16 healthy age-matched volunteers served as a control group. To clarify whether p70S6K activity is varying among CD4+ T-cell subsets, cell sorted CD4+CD25hi regulatory T cells (Tregs) and CD4+CD25− T cells were analyzed for p70S6K phosphorylation. Results Simultaneous analysis of p70S6K phosphorylation by phosphoflow cytometry and Western blot showed high correlation in peripheral blood mononuclear cells of renal transplant patients (r=0.91, P<0.001). Mammalian target of rapamycin inhibition was associated with marked reduction of p70S6K phosphorylation compared to healthy volunteers or RTX patients receiving calcineurin inhibitors (all P<0.001) but did not correlate with mTORi trough levels. Interleukin-2 production in mitogen-stimulated CD3+ T cells correlated with the degree of p70S6K phosphorylation in everolimus-treated patients. p70S6K phosphorylation in CD4+CD25hi Tregs was significantly lower compared to CD4+CD25− T cells (n=3). In mTORi treated RTX recipients, p70S6K phosphorylation was selectively reduced in CD4+CD25− T cells leaving CD4+CD25hi Tregs unimpaired. Conclusion Phosphoflow cytometric quantification of p70S6K phosphorylation may play an adjunct role to pharmacodynamically guide an individualized mTORi therapy. It may have potential to be used in purity testing of Treg suspensions generated for adoptive tolerogenic therapies.